Determination of thermal diffusivity of Basalt fiber reinforced epoxy composite using infrared thermography. (February 2019) - Kalyanavalli, V.; Ramadhas, T.K. Abilasha; Sastikumar, D.
Highlights: Experimental analysis to study the thermal properties of basalt composites. In-depth thermal diffusivity measurements by pulse thermography. In-plane thermal diffusivity by space resolved method. Abstract: In recent years, there is a great demand for ecofriendly, light weight and cost effective composites. Basalt fiber is one such naturally available fiber which offers exceptional properties over glass fibers. In this study a Basalt fiber reinforced composites were fabricated by vacuum bagging technique. Thermal properties of these composites were determined using infrared thermography. In-depth and in-plane thermal diffusivity were determined by using pulse thermography and space resolve method, respectively. The in-plane thermal diffusivity was determined in the transmission and reflection modes. In-depth thermal diffusivity was validated with Light flash method.